Gaps and Opportunities in HIV Service Delivery in High Volume HIV Care Centers in Liberia: Lessons From the Field - Mukhtar A. Adeiza; Ian Wachekwa; Cecilia Nuta; Sean Donato; Freda Koomson; Jane Whitney; Chelsea Plyler; Lila Kerr; Godsway Sackey; Elizabeth Dunbar; Kristina Talbert-Slagle; Robin Klar; et al. (Ubiquity Press, 2021)
Background: Human Immunodeficiency Virus (HIV) infection continues to have a profound humanitarian and public health impact in western and central Africa, a region that risks being left behind in the global response to ending the AIDS epidemic. In Liberia, where the health system is being rebuilt following protracted civil wars and an Ebola virus disease outbreak, the Resilient and Responsive Health System (RRHS) is assisting with quality HIV services delivery through support from PEPFAR and HRSA but gaps remain across the cascade of care from diagnosis to viral load suppression. Objective: To highlight gaps in HIV service delivery in Liberia, identify opportunities and offer recommendations for improving the quality of service delivery. Methods: A narrative review of relevant literature was conducted following a search of all local and online databases known to the authors. Findings: Antiretroviral therapy (ART) has transformed the HIV response in Liberia by averting deaths, improving quality of life, and preventing new HIV infections but critical gaps remain. These include weak HIV prevention and testing strategies; suboptimal ART initiation and retention in care; low viral load testing volumes, commodity supply chain disruptions and a HIV workforce built on non-physician healthcare workers. In the context of the prevailing socioeconomic, heath system and programmatic challenges, these will impact achievement of the UNAIDS targets of 95-95-95 by 2030 and ending the epidemic. Conclusion: Combination prevention approaches are necessary to reach the most at risk populations, while a robust health workforce operating through facilities and communities will be needed to reach people with undiagnosed HIV earlier to provide efficient and effective services to ensure that people know their HIV status, receive and sustain ART to achieve viral suppression to maintain a long and healthy life within the framework of overall health system strengthening, achieving universal health coverage and the sustainable development goal.